Individual differences in self-reported heat tolerance. Is there a link to the cardiocirculatory, thermoregulatory and hormonal response to endurance exercise in heat? - Niess, A. M.; Fehrenbach, E.; Roecker, K.; Lehmann, R.; Opavsky, L.; Dickhuth, H. H. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: Tolerance to exercise in heat exhibits great interindividual variability. We questioned whether individual differences in self-reported heat tolerance within a group of endurance trained athletes are linked to the cardiocirculatory, thermoregulatory and hormonal response to endurance exercise in heat. Methods: Using a rating scale to assess the individual degree of tolerance to exercise in heat we allocated 12 non-heat-acclimated trained runners into two groups of 5 highly heat tolerant (HHT) and 7 less heat tolerant (LHT) athletes. Both groups performed a 60-min treadmill run (velocity 90% of individual anaerobic threshold, room temperature and humidity 28°C and 50%, respectively). Results: Sweating rate did not differ between HHT (mean ± SEM: 0.44±0.02) and LHT (0.40±0.02 ml·kg-1·min-1). Compared to LHT, exercise-induced rises in core temperature (39.3±0.2/40.0±0.2°C), heart rate, plasma norepinephrine and cortisol were significantly lower in HHT, while epinephrine did not exhibit differences between the groups. In contrast, response of human growth hormone (hGH) was significantly more pronounced in HHT. Conclusion: Our initial results, obtained in a small group of endurance-trained runners, show that self-reported tolerance to exercise in heat is associated with an attenuated rise in body core temperature during prolonged exercise under elevated ambient temperatures. This finding in heat tolerant athletes is paralleled by a lower stress response as reflected by lower rises in heart rate and stress hormones such as norepinephrine and cortisol. The functional significance (i.e. with respect to sweating function) of the more pronounced response of hGH in heat tolerant athletes warrants further research.